Immunization status of children visiting a health centre in Uri, Jammu and Kashmir: reasons for drop-outs from immunization - Singh, Ankita; Senger, K. P. S.; Singh, Arvind K.; Singh, Ajay K. (International Journal Of Community Medicine And Public Health, 2017)
Background: Immunization is one of the most powerful and cost effective tools available to improve public and global health and is essential for every child’s life. This study aims to estimate the immunization status and factors effecting drop-outs from immunization in children residing in Uri, Jammu & Kashmir. Methods: It is a cross-sectional descriptive study, with sample-size of 480 children between 12 to 23 months of age. Immunization status was assessed depending upon coverage of four important vaccines given during primary immunization. Results: The study showed that total primary immunization status of Uri was 58.12% with 91.2% OPV, 88.1% BCG, 72.5% DPT and 58.8% measles immunization (CI= 95%, p<0.05). Factors effecting drop-outs were distantly located health centre (27.9%), poor motivation (33.12%), lack of awareness (9.77%), and parental refusal (in case of OPV was 5.35%) (CI= 95%, p<0.05). Literate mothers were more likely to get their children completely immunized. Gender Bias wasn’t observed. Conclusions: Findings suggest that immunization status needs to be improved by focussing on vaccines having low coverage (DPT and measles) by creating awareness and better out-reach facilities with the involvement of community workers.